Reevaluating the age of the Iberomaurusian in Morocco - Bouzouggar, A; Barton, R; Blockley, S; Bronk-Ramsey, C; Collcutt, S; Gale, R; Higham, T; Humphrey, L; Parfitt, S; Turner, E; Ward, S (Springer US, 2008)
Chronological evidence for the Iberomaurusian is currently very limited and there are problems with some of the published radiocarbon dates. In this paper we present new AMS dating results from well-stratified cave sequences at Ghar Cahal, Kehf el Hammar and Taforalt in northern and eastern Morocco. The longest of these sequences, from Taforalt, shows an intermittent occupation history spanning the period ca. 18,000 - 11,000 bp (radiocarbon determinations presented in this paper are expressed as ka bp or bp, whilst approximate calendar ages are expressed as Cal bp) with a marked intensification of cave use soon after ca. 13,000 bp. Using calibrated AMS ages in comparison to sea surface temperature evidence from the Alboran Sea core MD95-2043 and more generally to Greenland ice δⁱ⁸O core records, we suggest that there may have been a relationship, albeit a complex one, between climatic events and cave activity on the part of Iberomaurusian populations. La chronologie de l'Ibéromaurusien est actuellement très limitée et certaines dates de radiocarbone publiées sont problématiques. Dans cet article, nous présentons de nouvelles datations AMS (spectrométrie de masse par accélérateur) provenant de séquences bien stratifiées des grottes du nord et de l'oreintal est du Maroc: Ghar Cahal, Kehf el Hammar et Taforalt. La plus longue de ces séquences, celle de Taforalt, montre une occupation intermittente couvrant la période ca. 18,000 bp (dates de radiocarbone non corrigées1) avec une utilisation intensive de la grotte peu après ca. 13,000 bp (non corrigée). Ensuite, nous avons comparé les datations AMS corrigées aux indications de températures de surface marine calculées à partir du carottage MD95-2043 de la Mer d'Alboran et plus généralement, aux données de δⁱ⁸O des carottages de glace du Groenland. Nous en déduisons qu'il pourrait y avoir des rapports, quoique complexes, entre les événements climatiques et l'intensité des activités ibéromaurusiennes dans ces grottes.